Analisis Pengukuran Kinerja Anggaran Belanja Dengan Menggunakan Metode Value For Money Pada Dinas Pariwisata Kota Makassar Periode 2020-2022 - Rika Wulandari; Sabirin Iskandar; Fausiah Fausiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the performance of the Makassar City Tourism Office in 2020-2022 in terms of economic, efficiency and effectiveness elements. This research is a descriptive research study with the object under study is data on the realization of financial achievements contained in the Financial Report and Performance Report (LAKIN) of the Makassar City Tourism Office in 2020-2022. The data analysis technique used is quantitative descriptive analysis on economic, efficiency, and effectiveness measurements. Based on the results of the study, it shows that the performance of the Makassar City Tourism Office in terms of Economic, Efficiency and Effectiveness elements has almost met the requirements of Value for Money where each element almost reaches the maximum ratio value which is accompanied by budget savings every year. So it can be stated that the financial performance of the Makassar City Tourism Office almost meets the requirements of Value for Money where each allocated budget is able to be managed quickly in carrying out each program that has been determined.